Reduction of post-operative pain after tonsillectomy by a local mucosal flap – a prospective, randomized, controlled clinical trial on 100 adult patients. (3rd October 2018) - Linxweiler, Maximilian; Kühn, Jan Philipp; Wagner, Mathias; Al Kadah, Basel; Schick, Bernhard
Abstract: Background: Tonsillectomy is one of the most frequent operations in otorhinolaryngology being associated with intense post-operative pain and an impairment of swallowing and speech. Aims: To determine whether wound sealing with a local mucosal flap can improve patient rehabilitation. Materials and methods: The study was designed as a prospective, randomized, monocentric, controlled clinical trial including 100 patients. Patients were operated on using either conventional extracapsular tonsillectomy ( n = 50) or a modified technique with a local mucosal flap prepared from the posterior surface of the tonsil ( n = 50). Number of requested pain medications, local oedema, patient-reported pain level, post-operative haemorrhage, impairment of speech, swallowing and general condition were assessed. The study was registered at the German Clinical Trials Register. Results: The mucosal flap technique significantly reduced post-operative pain [2.94 (intervention group) vs. 4.61 (control group) in an numerical analogue scale, p < .001] and the number of pain medications [6 (intervention group) vs. 1 (control group), p < .001]. Conclusions: Wound sealing with a local mucosal flap can reduce post-operative pain in tonsillectomy patients and is recommended whenever anatomically feasible. Significance : This new tonsillectomy technique can help to reduce post-operative pain and thereby improve the patients' post-operative rehabilitation.